2023
DOI: 10.1039/d3nj01413d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the catalytic transfer hydrogenation of furfural to furfuryl alcohol over a N-doped carbon-supported Ni single atom catalyst from first principles

Abstract: The carbon-supported Ni-single atom catalysts provide a promising strategy for the selective hydrogenation of furfural to furfuryl alcohol, but the detailed mechanism is still unclear. To gain insights into the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…To determine the transfer reaction mechanism, Yang et al also carried out theoretical calculations on furfural transfer hydrogenation over Ni 1 /NC. 86 The results showed that the O−H bond of isopropanol was first activated and transferred to noncoordinated pyridinic N atoms, while Ni activated the C− H bond to form a metal−hydride bond. In the second stage, the H atoms were transferred from Ni sites to the carbonyl group of furfural, followed by the H transfer from the noncoordinated pyridinic N to the carbonyl oxygen.…”
Section: Furfural Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the transfer reaction mechanism, Yang et al also carried out theoretical calculations on furfural transfer hydrogenation over Ni 1 /NC. 86 The results showed that the O−H bond of isopropanol was first activated and transferred to noncoordinated pyridinic N atoms, while Ni activated the C− H bond to form a metal−hydride bond. In the second stage, the H atoms were transferred from Ni sites to the carbonyl group of furfural, followed by the H transfer from the noncoordinated pyridinic N to the carbonyl oxygen.…”
Section: Furfural Conversionmentioning
confidence: 99%
“…The difference was attributed to the lower steric hindrance and inertness of the Ni–N 3 sites. To determine the transfer reaction mechanism, Yang et al also carried out theoretical calculations on furfural transfer hydrogenation over Ni 1 /NC . The results showed that the O–H bond of isopropanol was first activated and transferred to noncoordinated pyridinic N atoms, while Ni activated the C–H bond to form a metal–hydride bond.…”
Section: Application Of Sacs In Biomass Chemical Conversionmentioning
confidence: 99%
“…More theoretical studies were conducted by Lai and others to elucidate mechanism for furfural hydrogenation by isopropanol over a Ni single atom supported on N-doped graphene catalyst. [127] They showed that isopropanol was activated by both Lewis acid NiN 4 single atom and the defected pyridinic sites of N-doped carbon. Interestingly, the authors proved that all these sites participate actively for transfer hydrogenation to carbonyl carbon of furfural.…”
Section: Mechanismmentioning
confidence: 99%